2004
DOI: 10.1098/rspb.2004.2855
|View full text |Cite
|
Sign up to set email alerts
|

Predation risk is an ecological constraint for helper dispersal in a cooperatively breeding cichlid

Abstract: Environmental conditions are thought to be responsible for the extent and benefits of cooperative breeding in many animal societies, but experimental tests are scarce. We manipulated predator pressure in the cooperatively breeding cichlid Neolamprologus pulcher in Lake Tanganyika, where predators have been suggested to influence helper and breeder survival, helper dispersal and group reproductive success. We varied the type and intensity of predation by releasing medium, large, or no predators inside large und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
250
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(259 citation statements)
references
References 52 publications
(76 reference statements)
6
250
2
1
Order By: Relevance
“…Our study generally confirms that kinship is an important component in cooperative systems, but remarkably relatedness may have effects contrary to predictions from conventional kin-selection theory, if coercion by dominants is involved. It is important to note here that group augmentation is likely to generate fitness benefits of helping in this species as well 24,48 , but due to our experimental design this mechanism cannot explain the differences found between the experimental treatments in this study. Rather, dominants and unrelated subordinates seem to trade different commodities reciprocally against each other, thereby generating fitness benefits to both.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our study generally confirms that kinship is an important component in cooperative systems, but remarkably relatedness may have effects contrary to predictions from conventional kin-selection theory, if coercion by dominants is involved. It is important to note here that group augmentation is likely to generate fitness benefits of helping in this species as well 24,48 , but due to our experimental design this mechanism cannot explain the differences found between the experimental treatments in this study. Rather, dominants and unrelated subordinates seem to trade different commodities reciprocally against each other, thereby generating fitness benefits to both.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the cooperative behaviour experimentally elicited in this study is of crucial importance for a test of the pay-to-stay hypothesis, as alloparental egg-care does not provide immediate fitness benefits to unrelated helpers, whereas it involves clear costs 36,37 . As this helping effort is hence altruistic, it can be selected for only if helpers receive other fitness benefits in return, which result from the tolerance in a safe territory that provides them with access to vital resources such as shelter and protection 19,29,48 , and opportunities to share in reproduction 49,50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in N. pulcher, there is a potential for conflict between helpers and breeders about the possible participation of helpers in reproduction. Breeder males threaten helpers with aggression and the risk of expulsion (Dierkes et al, 1999;Skubic et al, 2004), while helpers attempt to appease the breeders and reduce the risk of expulsion from the territory by helping and displaying submissive behaviour, depending on environmental constraints (Taborsky, 1985;Balshine-Earn et al, 1998;Heg et al, 2004a;. Buchner et al (2004) found higher cortisol (F) plasma levels in dominant individuals than in subordinates in N. pulcher, confirming a general rule found in many mammal and bird societies, where paternity is shared by dominants and subordinates and the social situation is therefore stressful for the dominants (Schoech et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Individual groups consist of a dominant breeding pair and up to 30 subordinates (25,26,30). Groups are frequently attacked by predatory fish (26), which significantly affects the survival probability of group members, especially small subordinates and fish devoid of protection through large conspecifics (31). Hence, membership in a group is a precondition for survival.…”
mentioning
confidence: 99%